1991
DOI: 10.1002/1520-6807(199110)28:4<310::aid-pits2310280405>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of high school students with a history of grade retention

Abstract: The present study examines high school students with a prior history of grade retention (N = 38) compared to a matched control group of nonretained students. The retained students were lower on a number of scholastic variables (i.e., achievement, intelligence, grades), more often absent from school, and lower on three subscales of a self-esteem measure (the Self-perception Profile for Adolescents). The authors explored the correlates of grade retained with the measured variables and found that the later a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Previous studies have found poor outcomes for retained students and have discouraged the use of retention as an intervention for low-achieving and socially and emotionally maladjusted children and adolescents (see Hagborg et al, 1991;Jimerson, 1999;Jimerson et al, 1997;Meisels & Liaw, 1993;Niklason, 1987;Pagani et al, 2001;Sandoval & Fitzgerald, 1985;Silberglitt et al, 2006). Results from the present study show that retained students had lower reading achievement in eighth grade and slower reading growth rates in secondary school compared to similar promoted peers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found poor outcomes for retained students and have discouraged the use of retention as an intervention for low-achieving and socially and emotionally maladjusted children and adolescents (see Hagborg et al, 1991;Jimerson, 1999;Jimerson et al, 1997;Meisels & Liaw, 1993;Niklason, 1987;Pagani et al, 2001;Sandoval & Fitzgerald, 1985;Silberglitt et al, 2006). Results from the present study show that retained students had lower reading achievement in eighth grade and slower reading growth rates in secondary school compared to similar promoted peers.…”
Section: Resultsmentioning
confidence: 99%
“…Alexander et al, 2003;Silberglitt, Jimerson, Burns, & Appleton, 2006). Longitudinal studies usually report negative findings for the effects of grade retention on retained students' academic achievement and social-emotional health in middle or high school (Hagborg, Masella, & Palladino, 1991;Jimerson, 1999;Jimerson et al, 1997;Meisels & Liaw, 1993;Pagani, Tremblay, & Vitaro, 2001;Sandoval & Fitzgerald, 1985), and there is a strong relationship between grade retention and dropping out of school (Jimerson, Anderson, & Whipple, 2002). Jimerson's (2001) meta-analysis, which included the studies examined by Holmes (1989;Holmes & Matthews, 1984), found negative effects for academic achievement (effect size ¼ À.39) and social adjustment (effect size ¼ À.22) measures; the effect of retention on reading (effect size ¼ À.54) was only exceeded by an effect on attendance (effect size ¼ À.65; based on only two effects).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A finding of no effect is most common for behavioral engagement (Ferguson, 1991; Gottfredson et al, 1994; Pierson & Connell, 1992), liking for or interest in school (Alexander et al, 1994; Hagborg et al, 1991), and academic self-efficacy (Alexander et al 1994; McCoy & Reynolds, 1999; Phelps, Dowdell, Rizzo, Ehrlich, & Wilczenski, 1992). The few findings of negative effects tend to come from studies with poor controls for preselection differences (Hagborg et al, 1991; Pianta et al, 1997). Importantly, a study using strong controls for preretention vulnerabilities reported positive effects of retention in the kindergarten grades on academic self-efficacy 2 and 4 years later (Hong & Yu, 2008).…”
Section: Previous Research On Retention Effects On Psychosocial Outcomesmentioning
confidence: 99%
“…In a number of studies, an external locus of control orientation has been found to be associated with factors such as low achievement in school, depression, and delinquency (Hagborg, Masella, Palladino, & Shepardson, 1991;McCauley, Mitchell, Burke, & Moss, 1988;Parrott & Strongman, 1984;Shaw & Scott, 1991;Sohlberg, 1989;Van-Boxtel & Monks, 1992). Findings such as these suggest the importance of developing of a more internal locus of control orientation, which has been associated with academic achievement, positive emotional status, and lower rates of delinquency.…”
Section: Locus Of Controlmentioning
confidence: 99%